Exploring the Interplay of Perceived Organizational Support, Fringe Benefits, Work Resilience, and Self-Efficacy in Predicting Employee Performance - Cindy Pramita; Budi Eko Soetjipto (CV. Proaksara Global Transeduka, 2025)
In an era of increasingly dynamic business competition, improving employee performance is a top priority for organisations. One strategic approach that has been widely researched is Perceived Organizational Support (POS), which is the employee's perception of the extent to which the organisation values their contribution and cares about their well-being. This study aims to explore the relationship between POS, fringe benefits, work resilience, and self-efficacy in predicting employee performance. This study uses a qualitative approach through a systematic literature study of various relevant national and international scientific journals. The results show that POS has a positive effect on employee performance, and this effect is mediated by the presence of fringe benefits. Meanwhile, work resilience and self-efficacy act as moderator variables that strengthen the relationship between POS and performance. The implications of this study emphasise the importance of organisations in creating a supportive work environment, providing competitive benefits, and empowering the psychological aspects of employees to increase work productivity in a sustainable manner. The findings can serve as a basis for developing more effective and long-term orientated human resource management strategies.